If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -26 = 72 Reorder the terms: -26 + 3x = 72 Solving -26 + 3x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + 3x = 72 + 26 Combine like terms: -26 + 26 = 0 0 + 3x = 72 + 26 3x = 72 + 26 Combine like terms: 72 + 26 = 98 3x = 98 Divide each side by '3'. x = 32.66666667 Simplifying x = 32.66666667
| (24x)^2+8x/(4x) | | 1=6m+3-2 | | 1(3x-1)+1(2x+3)=2 | | -x/3=10 | | -3(x-8)=38-5x | | 2x^2-11x+20=5 | | 8x^2+7x+2=0 | | b+1+5=8 | | 0=24x^2+8x/4x | | 5x+2x-9-21=180 | | 5x(x+3)-7(x+5)=5 | | 10=3r-5r | | 1/2(4x-10)=x | | 17=1-5x-3x | | R=a+c/2b | | 0=-5k-k | | 6(1-6n)-3=-34+n | | 4-4x=10x-10 | | 7=n+6n | | -6n-3n=-18 | | 5x^3-9x^2+4x=0 | | -15=6a+5-2a | | (5x-21)+(2x-9)=180 | | Y^2-4x^2-12y-16x+4=0 | | 7=p-3-6p | | 3xsquared+15x+14=4xsqaured | | -2=5x-3x | | 3x+26=72 | | 3xsquared+15x+14=4xsquared | | X=-22+3x | | -2(-7n+1)=-6(9-2n)+9n | | 5+3(9-x)=7(3+x)+1 |